2010
DOI: 10.1016/j.pain.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among alexithymia and pain intensity, pain interference, and vitality in persons with neuromuscular disease: Considering the effect of negative affectivity

Abstract: Alexithymia, the inability to identify or label emotions, has been shown to be associated with pain in patients with a number of chronic pain conditions. We sought to: (1) replicate this association in samples of persons with chronic pain secondary to neuromuscular disease; (2) extend this finding to other important pain-related measures, and (3) to determine whether relationships among alexithymia and study variables existed after controlling for negative affect. One hundred and twenty-nine individuals with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 37 publications
6
40
2
3
Order By: Relevance
“…Moreover, pain, which is one of the most distressing symptoms affecting about 50% of cancer patients (World Health Organization, 1990), is strictly associated with alexithymia in several chronic pain illnesses (Glaros & Lumley, 2005;Hosoi et al, 2010;Lumley, Smith, & Longo, 2002;Mehling & Krause, 2005;Neyal Muftuoglu, Herken, Demirci, Virit, & Neyal, 2004;Pecukonis, 2009;Porcelli et al, 2007;Sipila¨et al, 2001). The present article reports the findings of the additional analysis of a previously published dataset (Tulipani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pain, which is one of the most distressing symptoms affecting about 50% of cancer patients (World Health Organization, 1990), is strictly associated with alexithymia in several chronic pain illnesses (Glaros & Lumley, 2005;Hosoi et al, 2010;Lumley, Smith, & Longo, 2002;Mehling & Krause, 2005;Neyal Muftuoglu, Herken, Demirci, Virit, & Neyal, 2004;Pecukonis, 2009;Porcelli et al, 2007;Sipila¨et al, 2001). The present article reports the findings of the additional analysis of a previously published dataset (Tulipani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The independent effect of alexithymia on pain perception has rarely been examined so far. Hosoi et al examined 129 patients with neuromuscular disorders and found that the association between alexithymia and pain intensity is greatly diminished when controlling for baseline negative affect (19). Another shortcoming of previous studies is that most of them evaluated the output of pain without considering the inputs of pain (13).…”
Section: Introductionmentioning
confidence: 99%
“…Specific aspects of alexithymia such as enhanced fantasy and difficulty identifying emotions were significantly associated with somatization along with other prominent symptoms such as pain, anxiety etc. These pathways were facilitated by negative affectivity [34,35] with medically unexplained symptoms [36,37].…”
Section: Discussionmentioning
confidence: 99%